Special stains in study of infertile endometrium - Halgale, Mohasin Jakirhusain; Jadhav, Meenal Vitthal; Kadgi, Nalini V (Annals of Pathology and Laboratory Medicine, 2018)
Background: Integrity of ovarian function is a prerequisite for successful implantation of ovum. The subtle changes in ovarian function can be detected by studying endometrial carbohydrates with special stains. Material and methods: 87 infertile and 30 normal endometria were studied with the help of Hematoxylin& Eosin ( H & E) stain and special stains like Best Carmine, Alcian blue PAS (with and without diastase digestion) and reticulin stain. Results: Special stains were useful in emphasizing the cyclical activity of carbohydrates and stroma in normal endometrium. In infertile endometrium, they helped in precise classification and detection of corpus luteal deficiency, at times (8.7% cases) missed on routine H& E stain . Intrinsic abnormalities like polyps and tuberculous granulomas could be detected with ease on reticulin stain. On application of special stains, incidence of corpus luteal deficiency was 27.5%, and that of anovulatory infertility and normal secretory endometrium was 34.5% each.Â Conclusion: The special stains helped in detecting precise endometrial response and added to the information obtained by routine H&E stain. DOI:10.21276/APALM.1725